Attracting FDI through BITs and RTAs: Does treaty content matter? - Axel Berger; Matthias Busse; Peter Nunnenkamp; Martin Roy (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
The authors analyze empirically whether the impact of BITs and RTAs on bilateral FDI flows depends on the inclusion of two legal innovations: investor-state dispute settlement (ISDS) and pre-establishment national treatment (NT) provisions. Indeed, they find strong evidence that liberal NT provisions promote FDI. ISDS mechanisms appear to play a minor role. Surprisingly, the impact of similar investment provisions on FDI depends on whether these provisions are contained in RTAs or BITs.
Keywords: 330